2008
DOI: 10.1007/s11207-008-9261-1
|View full text |Cite
|
Sign up to set email alerts
|

Presence of LaO, ScO and VO Molecular Lines in Sunspot Umbral Spectra

Abstract: High-resolution Fourier Transform Spectrometer sunspot umbral spectra of the National Solar Observatory/National Optical Astronomy Observatory at Kitt Peak were used to detect rotational lines from 19 electronic transition bands of the molecules LaO, ScO and VO, in the wavenumber range of 11 775 to 20 600 cm −1 . The presence of lines from the following transitions is confirmed: 0) and B 2 Σ + -X 2 Σ + (0, 0) of ScO; and C 4 Σ − -X 4 Σ − (0, 1; 1, 0; 0, 2) and (2, 0) of VO. However, the presence of A 2 Π r3/2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 23 publications
2
12
0
Order By: Relevance
“…The effective rotational temperatures had been estimated for D-A (0,0) and F -A (0,0) bands of AlF to be 1240 ± 120 K and 2390 ± 400 K respectively by Bagare et al (2006). Mulchaey (1989) has estimated the average temperature of the FeH molecule for the two P(J ) branches of the (7/2)-(7/2) sub-band to be 1740 ± 100 K. The lower value of T (1737 K) evaluated for SrF in the present study is therefore similar to that of the B 2 + -X 2 + (0, 1) band of LaO reported by Sriramachandran et al (2008) and of FeH (Mulchaey 1989). It is known that even in the photosphere, temperatures as low as 3800 K had been measured from the lines of CO.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The effective rotational temperatures had been estimated for D-A (0,0) and F -A (0,0) bands of AlF to be 1240 ± 120 K and 2390 ± 400 K respectively by Bagare et al (2006). Mulchaey (1989) has estimated the average temperature of the FeH molecule for the two P(J ) branches of the (7/2)-(7/2) sub-band to be 1740 ± 100 K. The lower value of T (1737 K) evaluated for SrF in the present study is therefore similar to that of the B 2 + -X 2 + (0, 1) band of LaO reported by Sriramachandran et al (2008) and of FeH (Mulchaey 1989). It is known that even in the photosphere, temperatures as low as 3800 K had been measured from the lines of CO.…”
Section: Resultssupporting
confidence: 87%
“…In order to evaluate the confidence level for presence of the systems studied, we adopted the method of coincidences described in detail by Engvold et al (1980) and Sriramachandran et al (2008). The number of chance coincidences (C index) may be expressed as…”
Section: Srf Solar Identificationmentioning
confidence: 99%
“…For TiO molecule, the most studied species, the lower limit of temperature is 2980 ± 200 K reported by Sotirovski (1971). The range of effective rotational temperature of metal oxides LaO, ScO and VO molecules reported by Sriramachandran et al (2008) shows an excellent agreement with that of effective vibrational temperature of 90 ZrO molecule. Further, the effective temperatures of LaO, ScO and VO molecular bands suggest that they are confirmed to be present in various heights of the cool regions of sunspot atmosphere.…”
Section: Resultssupporting
confidence: 72%
“…This result agrees well with the value found by Sotirovski (1971) using TiO molecule and its temperature is 2980 ± 200 K. The lower limit of effective rotational temperature estimated for the CrH molecule agrees well with the average value of temperature for FeH found by Mulchaey (1989). The higher temperature value of 2246 K was claimed by Sriramachandran et al (2008) for the band C 4 − -X 4 − (1, 0) of VO molecule using the well resolved P (J ) and R(J ) branch lines. Bauschlicher et al (2001) have pointed out that the surface temperature of M-star drops below approximately 1800 K; metal oxides such as TiO and VO are replaced by metal hydrides CrH and FeH.…”
Section: Resultsmentioning
confidence: 81%
“…This region is bounded at short wavenumbers by the strong (0, 1) head of the TiO γ bands (Ram et al 1999) and at long wavenumbers by the increasing strength of lines of the reddegraded bands of the v = −1 sequence of the CaH (A-X) bands and the v = 0 sequence of the TiO γ bands. We have recently identified the bands of LaO, ScO, VO (Sriramachandran et al 2008), SrF ), BeH (Shanmugavel et al 2008) andCrH (Engvold et al 1980) molecular lines in these red and infrared regions. The spectrum is available in electronic form at NSO web site, operated by the Association of Universities for Research in Astronomy.…”
Section: Sunspot Umbral Spectramentioning
confidence: 93%